2022
DOI: 10.1167/jov.22.9.3
|View full text |Cite
|
Sign up to set email alerts
|

Transient attention equally reduces visual crowding in radial and tangential axes

Abstract: Crowding refers to the failure to identify a peripheral object due to its proximity to other objects (flankers). This phenomenon can lead to reading and object recognition impairments and is associated with macular degeneration, amblyopia, and dyslexia. Crucially, the maximal target–flanker spacing required for the crowding interference (critical spacing) increases with eccentricity. This spacing is also larger when target and flankers appear along the horizontal meridian (radial arrangement) than when the fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…The present findings explain the inconsistent results of spatial attention investigations in crowding and attribute them to variations in the locus of attention. Consistent with the present study, previous studies using various cue and target types showed that cueing attention at the target location did not reduce crowding interference ( Scolari et al, 2007 ; Strasburger & Malania, 2013 ), whereas cueing attention at location inner to the target reduced crowding interference ( Grubb et al, 2013 ; Kewan-Khalayly et al, 2022 ; Yeshurun & Rashal, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings explain the inconsistent results of spatial attention investigations in crowding and attribute them to variations in the locus of attention. Consistent with the present study, previous studies using various cue and target types showed that cueing attention at the target location did not reduce crowding interference ( Scolari et al, 2007 ; Strasburger & Malania, 2013 ), whereas cueing attention at location inner to the target reduced crowding interference ( Grubb et al, 2013 ; Kewan-Khalayly et al, 2022 ; Yeshurun & Rashal, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the compelling evidence for an attentional effect on spatial resolution, investigations of attentional manipulation in crowding have yielded mixed results. Some studies have shown that attention decreases critical spacing (i.e., the minimum spacing required for crowding) ( Grubb, Behrmann, Egan, Minshew, Heeger, & Carrasco, 2013 ; Kewan-Khalayly, Migó, & Yashar, 2022 ; Yeshurun & Rashal, 2010 ); however, other studies have failed to demonstrate an effect on crowding ( Scolari, Kohnen, Barton, & Awh, 2007 ; Strasburger, 2005 ). One possible reason for this inconsistency is that the locus of attention with respect to the target could have varied across these studies and therefore caused the attentional effect on crowding.…”
Section: Introductionmentioning
confidence: 99%
“…Our data set includes a large number of participants (21 that were included in the analyses presented here) and a substantial amount of data per subject (3,840 trials of the anticueing task). In comparison, recent studies of the effects of spatial attention on crowding (e.g., Yeshurun & Rashal, 2010 ; Albonico et al., 2018 ; Kewan-Khalayly, Migó, & Yashar, 2022 ) included 16 or fewer subjects per main experiment and 1,280 or fewer trials per subject. Our study therefore has high sensitivity for detecting possible cueing effects on RT and critical spacing.…”
Section: Discussionmentioning
confidence: 99%
“…There is much debate about how attention affects visual crowding in general and critical spacing in particular. Most studies of the effects of involuntary attention have found enhanced perceptual performance on crowding tasks, and some of these also reported significant effects of involuntary attention on critical spacing ( Yeshurun & Rashal, 2010 ; Rashal & Yeshurun, 2014 ; Kewan-Khalayly, Migó, & Yashar, 2022 ) while others did not ( Felisberti, Solomon, & Morgan, 2005 ; Scolari, Kohnen, Barton, & Awh, 2007 ). Yeshurun and Rashal (2010) hypothesized that they observed a significant decrease in critical spacing with involuntary attention while other investigators did not because their peripheral cue did not act as a forward mask on the processing of the subsequently presented target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation